REKAYASA KONSTITUSIONAL ATAS POLITIK HUKUM PEMILU DI INDONESIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 135/PUU-XXII/2024 - Budiarti, Budiarti; Hisbullah, Hisbullah; Patodongi, Andi Wanuawali (JIL : Journal of Indonesian Law, 2025)
This study is motivated by the dynamic relationship between the role of the Constitutional Court and the consolidation of democracy in Indonesia, particularly in the context of elections, which often become an arena for tension between political interests and constitutional principles. The main objective of this study is to analyze the extent to which the Constitutional Court's decisions contribute to strengthening the democratic system or, conversely, open the door to practices that have the potential to undermine the quality of democracy. Using a systematic literature review approach, this study critically examines academic literature and previous research findings that discuss the function, role, and implications of Constitutional Court decisions within the framework of democracy and the rule of law theories. The main findings show that the Constitutional Court has played an important role in maintaining the integrity of the electoral process, expanding access to constitutional justice, and correcting policies that potentially violate citizens' political rights. However, there are also indications that some of the decisions are ambiguous and open to debate regarding the independence of the judiciary and the relationship between law and politics. The contribution of this research lies in providing a comprehensive mapping of the Constitutional Court's position as a key actor in Indonesian democracy, while also offering a critical reflection on the institutional challenges it faces. The implications of this study underscore the importance of strengthening institutional capacity, transparency of decisions, and the need for a follow-up research agenda that examines the long-term impact of the Constitutional Court's role on the quality of democracy and governance in Indonesia.